2015
DOI: 10.1021/acs.analchem.5b03180
|View full text |Cite
|
Sign up to set email alerts
|

Investigating Therapeutic Protein Structure with Diethylpyrocarbonate Labeling and Mass Spectrometry

Abstract: Protein therapeutics are rapidly transforming the pharmaceutical industry. Unlike for small molecule therapeutics, current technologies are challenged to provide the rapid, high resolution analyses of protein higher order structures needed to ensure drug efficacy and safety. Consequently, significant attention has turned to developing new methods that can quickly, accurately, and reproducibly characterize the three-dimensional structure of protein therapeutics. In this work, we describe a method that uses diet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
64
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 38 publications
(66 citation statements)
references
References 60 publications
2
64
0
Order By: Relevance
“…The modification percentage of each amino acid was determined in the same manner as described previously 21-25 Briefly, the ion abundance of each peptide of interest (i.e. labeled or unlabeled) was determined from extracted ion chromatograms (e.g.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The modification percentage of each amino acid was determined in the same manner as described previously 21-25 Briefly, the ion abundance of each peptide of interest (i.e. labeled or unlabeled) was determined from extracted ion chromatograms (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Our group has found that diethylpyrocarbonate (DEPC) is a valuable pseudo‐selective reagent for studying protein/protein interactions. 19-25 DEPC has some advantages over other non‐selective reagents, such as hydroxyl radicals, in that it requires no special equipment (e.g. laser or synchrotron), and it results in only a single reaction product, thereby simplifying MS analyses and improving detection sensitivity.…”
mentioning
confidence: 99%
“…For reagents like DEPC that are inherently less reactive than hydroxyl radicals and carbenes, the effect of primary or tertiary structure might be expected to be more pronounced since changes in the pK a values of a given residue lead to changes in its protonation state and thus nucleophilicity. The relatively poor correlation observed between SASA and the DEPC reactivity of Ser and Thr residues [58, 59, 73] might imply that the microenvironment around these amino acids, as formed by a protein’s tertiary structure, tunes their reactivity.…”
Section: Factors Affecting Covalent Labeling Reactivitymentioning
confidence: 99%
“…As a complement to free-radical footprinting, a variety of chemical reagents that target amino acid residues in a site-specific manner (e.g., N -ethylmaleimide 27 and diethylpyrocarbonate 28-29 ) can also provide information on site-specific solvent accessibility but react with protein substrates more slowly than do free radicals. 30 In this work, we performed carboxyl group footprinting with glycine ethyl ester (GEE) to corroborate the findings from HDX and FPOP, taking advantage of the presence of the many Asp/Glu residues in the flexible loops of IL-6R.…”
Section: Introductionmentioning
confidence: 99%